A Feasibility Study on Star Dustpan - Domingo, Gay R.; Garcia, Blessie Marie T.; Santos, Josephine C. (Diliman, Quezon City College of Engineering, 2001)
Star Dustpan, the Improved Dustpan with Wheels was invented by Mr. Guilermo Chua, one of the directors of the Filipino Inventor's Society, in his pursuit of further improvements of products with much consideration to ease and convenience of use. In the Market Feasibility Study, the past demand was determined through the number of households excluding class E and the average buying frequency. The historical demand was used to forecast the demand trend for the next five years. The forecasting techniques used were the linear regression after evaluating several forecasting methods. The forecasted demand graph showed that there is an increasing demand for the next five years. Industry Analysis shows that the current supply of dustpans is scarce and that there is a large gap between the demand and supply. The forecasted supply, also determined using linear regression, showed an increasing trend. The target market comprises the residential or household, income classes A, B, C, and D and plastic dustpan users. The demand for the product was determined to be great and the limiting factor for the market share to be captured is the projected capacity of the company. The market share for years 2002 to 2006 are as follows: *.90%, 9.66%, 10.48%, 11.37% and 12.34%. The projected production volume of the company is 253,000 for the first year, 278,300 for the next year 306,130 for the third year, 336,130 for the fourth year and 370,392 on the fifth year. The study proponents evaluated the 4Ps marketing strategies. In the Channel Analysis, it was determined that a two-level channel would be appropriate, wherein there are two middlemen, a wholesaler and a retailer. A selective distribution should be implemented since dustpans are classified as a durable shopping item. The distribution centers for wholesaler and retailers must be located in areas of greater density in terms of the market determinants. The amount of money allocated for marketing the product is about 0.5% of the annual sales. For the first year, the marketing budget amounted to P69,575. This amount is allocated to trade offers, promotional materials and labor for marketing. The total project cost for each alternative was computed. The costs covered are the fixed investment, working capital, venture initiation and the contingency cost. The total project cost for alternatives 1, 2 and 3 were computed as P15,226,302.98, P14,181,609.20 and P16,527,612.59 respectively. It can be observed that alternative 2 incurred the lowest total project cost, however, the cost of choosing alternative 2 is only cheaper by only P1,044,693.78 compared to the second cheapest alternative which is alternative 1. Taking into consideration the cost of possible expansion, it would be worth investing on alternative 1. In the Organizational Study, the form of ownership most appropriate for the project is the sole proprietorship, The proposed organization is the organization that can perform in the most effective manner with the fewest men possible and is considered most appropriate for the project. The proposed organization consists of the manager/owner, operations supervisor, secretary/clerk, maintenance personnel, driver, machine operators and assembly worker. In the Financial Feasibility Study, a pro forma income statement, cash flows projection and pro forma balance sheet were presented. The financial statements showed a positive and appreciable income even in the first year of operation. To finance the project, equity financing and debt loan financing will be used. 30% of the total project cost will be financed using owner's equity while the remaining 70% will be covered through debt loan financing. The chosen loaning agency to finance 70% project cost is the Development Bank of the Philippines with 15% annual interest. The repayment period is ten years and the repayment shall be in pesos. A net Present Value of P5,866,421.16 was computed at MARR = 35%. The internal rate of return was computed to be 64.95%. The results of different tests and ratios are generally of favorable trend. The payback period is 1.73 years; this means that it would take Star Dustpan Mfg 1.73 years to recover its entire cost of investment. In the Social Profitability Study, the study proponents enumerated and measured the costs and benefits of the project to the society. It was found that the benefits far outweigh the costs. It is also worth mentioning the benefits that are not quantifiable which includes: increased consumer awareness regarding ergonomic issues, generation of new jobs--salaries/benefits, portability and ease in cleaning, increased awareness of plastic recycling, influence on prices of similar products, among others. The results of the Market Feasibility Study, Technical Feasibility Study, Financial Study and Social Profitability Study confirm that the project is commercially profitable and socially profitable.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Cleaning machinery and appliances industry; Participatory monitoring and evaluation (Project management)